A policy model to analyze macroprudential regulations and monetary policy - Sami Alpanda; Gino Cateau; Césaire Meh (Bank of Canada, 2014)
We construct a small-open-economy, New Keynesian dynamic stochastic generalequilibrium model with real-financial linkages to analyze the effects of financial shocks and macroprudential policies on the Canadian economy. Our model has four key features. First, it allows for non-trivial interactions between the balance sheets of households, firms and banks within a unified framework. Second, it incorporates a risk-taking channel by allowing the risk appetite of investors to depend on aggregate economic activity and funding conditions. Third, it incorporates long-term debt by allowing households and businesses to pay back their stock of debt over multiple periods. Fourth, it incorporates targeted and broader macroprudential instruments to analyze the interaction between macroprudential and monetary policy. The model also features nominal and real rigidities, and is calibrated to match dynamics in Canadian macroeconomic and financial data. We study the transmission of monetary policy and financial shocks in the model economy, and analyze the effectiveness of various policies in simultaneously achieving macroeconomic and financial stability. We find that, in terms of reducing household debt, more targeted tools such as loan-to-value regulations are the most effective and least costly, followed by bank capital regulations and monetary policy, respectively.
Keywords: E44; F41; E32; E17; 330; Economic models; Financial system regulation and policies